Population pharmacokinetics of sildenafil in extremely premature infants. Issue 12 (15th December 2019) - Gonzalez, Daniel; Laughon, Matthew M.; Smith, P. Brian; Ge, Shufan; Ambalavanan, Namasivayam; Atz, Andrew; Sokol, Gregory M.; Hornik, Chi D.; Stewart, Dan; Mundakel, Gratias; Poindexter, Brenda B.; Gaedigk, Roger; et al.
Abstract : Aims: To characterize the population pharmacokinetics (PK) of sildenafil and its active metabolite, N‐desmethyl sildenafil (DMS), in premature infants. Methods: We performed a multicentre, open‐label trial to characterize the PK of sildenafil in infants ≤28 weeks gestation and < 365 postnatal days (cohort 1) or < 32 weeks gestation and 3–42 postnatal days (cohort 2). In cohort 1, we obtained PK samples from infants receiving sildenafil as ordered per the local standard of care (intravenous [IV] or enteral). In cohort 2, we administered a single IV dose of sildenafil and performed PK sampling. We performed a population PK analysis and dose‐exposure simulations using the software NONMEM®. Results: We enrolled 34 infants (cohort 1 n = 25; cohort 2 n = 9) and collected 109 plasma PK samples. Sildenafil was given enterally (0.42–2.09 mg/kg) in 24 infants in cohort 1 and via IV (0.125 or 0.25 mg/kg) in all infants in cohort 2. A 2‐compartment PK model for sildenafil and 1‐compartment model for DMS, with presystemic conversion of sildenafil to DMS, characterized the data well. Coadministration of fluconazole ( n = 4), a CYP3A inhibitor, resulted in an estimated 59% decrease in sildenafil clearance. IV doses of 0.125, 0.5 and 1 mg/kg every 8 hours (in the absence of fluconazole) resulted in steady‐state maximum sildenafil concentrations that were generally within the range of those reported to inhibit phosphodiesterase type 5 activity in vitro. Conclusions: We successfully characterized the PK of sildenafil and DMS in premature infants and applied the model to inform dosing for a follow‐up, phase II study.